Effect of chemical treatment on mechanical and physical properties kenaf fiber reinforced polyurethane (PU) composite - Gopinathan A/L Ganesan (2023)
The main purpose of this thesis is to study the effect of chemical treatment on mechanical and physical properties kenaf fiber reinforced composite. The sample preparation was done using polyurethane (PU) added to it at varies amount to study composite properties. There are 3 samples had been prepared with different composition of treated and untreated kenaf fiber with polyurethane. The samples had been tested for impact and hardness analysis.